Nilai-Nilai Pendidikan Islam dalam Film Kartun Nussa Dan Rara dan Dampaknya Terhadap Pengetahuan Agama Islam Siswa Kelas V SDN 2 Toronipa - Stefani; Karim; Sufiani (Tarbiyatul Akhyar: Jurnal Pendidikan, 2025)
This study aims to analyze the Islamic educational values contained in the cartoon film Nussa and Rara Season 2 and their impact on the Islamic knowledge of fifth-grade students at SDN 2 Toronipa. The method used is content analysis. Film contains various Islamic educational values, including religious values such as monotheism and faith in God, worship values such as prayer and dhikr, and moral values such as good manners or good behavior, cleanliness, honesty, and asking permission. These values are conveyed through a story that is relatable and easy to understand for children. Furthermore, watching this film has a positive impact on students' Islamic religious knowledge, increasing their understanding of the concept of monotheism, enthusiasm for worship, memorization of dhikr, and good, clean, and religious attitudes. Thus, the implications of this research indicate that audio-visual media such as cartoons, packaged in an educational and Islamic manner, can be an effective alternative learning strategy in elementary schools.